Os bebês nas instituições de educação infantil: mapeando a produção acadêmica - Zucoloto, Alexandra Santuzzi (2021)
This study, of a bibliographic nature, aims to investigate how babies have been referenced in the national normative documents, as well as in the academic productions, in the field of early childhood education, having as a reference the database from Portal da Capes (master theses and doctoral dissertations) related to the period between 2010 and 2018, from the descriptors: "babies" AND "early childhood education"; "babies" AND "childhoods" and "kindergarten". For the data treatment, the software NVivo was used as a tool that enables to structure and present the volume of information and data of the study portrayed through "word clouds", "word trees" or "tree maps", showing the frequency of a given information. Among the main conclusions, it is highlighted the few references to the babies in the documents that discuss or legislate about the early childhood education. In the master theses and doctoral dissertations analyzed, the main theoretical and methodological approaches used in the studies that consider the babies show their conception anchored by the assumptions of Sociology of Early Childhood, Pedagogy of Early Childhood, Psychology and Psychoanalysis. Although it was identified a concern in defining the age of babies, there is no consensus among the researchers investigated. This shows to be a low-explored field from the academic point of view, demanding new problematizations and studies about babies from/in early childhood education.